2007
DOI: 10.5414/cpp45583
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, vehicle-controlled, half-side comparison with a herbal ointment containing Mahonia aquifolium, Viola tricolor and Centella asiatica for the treatment of mild-to-moderate atopic dermatitis

Abstract: Objective: Only a few clinical trials have been published on the topical treatment of atopic dermatitis with herbal ointments. An ointment containing extracts from Mahonia aquifolium, Viola tricolor and Centella asiatica has previously been studied in open uncontrolled trials with children. However, no data exist on adult patients in a randomized controlled trial. Methods: A total of 88 patients with mild-to-moderate atopic dermatitis were enrolled in a double-blind, vehicle-controlled, randomized, half-side c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…Mahonia aquifolium demonstrated contrasting results: in an open-label trial in adults, significant improvements were reported in eczema area, severity index scores, and patient satisfaction on the basis of a posttreatment questionnaire, 87 whereas a randomized, double-blind, vehicle-controlled, half-side comparison with an herbal ointment containing M aquifolium, Viola tricolor, and Centella asiatica reported no statistical improvement compared with placebo in either primary skin symptoms or secondary assessment of pruritus, effectiveness, and tolerability. 88 Lyophyllum decastes extracted from Hatakeshimeji mushrooms effectively lowered total skin severity scores and serum IgE levels through its inhibitory action on the T H 2 immune response. 89 Konjac ceramide orally administered favored a shift toward the T H 1 pathway and demonstrated improvements in the Score of Atopic Dermatitis for skin symptoms, decreased skin responses to skin prick testing, and decreased dust mite specific IgE production.…”
Section: Asthmamentioning
confidence: 99%
“…Mahonia aquifolium demonstrated contrasting results: in an open-label trial in adults, significant improvements were reported in eczema area, severity index scores, and patient satisfaction on the basis of a posttreatment questionnaire, 87 whereas a randomized, double-blind, vehicle-controlled, half-side comparison with an herbal ointment containing M aquifolium, Viola tricolor, and Centella asiatica reported no statistical improvement compared with placebo in either primary skin symptoms or secondary assessment of pruritus, effectiveness, and tolerability. 88 Lyophyllum decastes extracted from Hatakeshimeji mushrooms effectively lowered total skin severity scores and serum IgE levels through its inhibitory action on the T H 2 immune response. 89 Konjac ceramide orally administered favored a shift toward the T H 1 pathway and demonstrated improvements in the Score of Atopic Dermatitis for skin symptoms, decreased skin responses to skin prick testing, and decreased dust mite specific IgE production.…”
Section: Asthmamentioning
confidence: 99%
“…Klövekorn and colleagues 436 conducted a placebo-controlled within-person trial in south Germany. A herbal topical cream available in Germany as Ekzevowen derma ® , in the UK as Linderma ® and in the USA as Dermavex ® (Weber & Weber GmbH & Co.) was used as the treatment.…”
Section: Studiesmentioning
confidence: 99%
“…In more recent randomized, placebo- or active drug-controlled studies on HMs, Xiao-Feng-San, TJ-15, and TJ-17 resulted in significantly improved clinical symptom scores and pruritus scores 6, 15. Furthermore, some individual herbs that benefit AD patients include St John’s wort, licorice, and mahonia 16, 17, 18. The most commonly proposed mechanism of HMs is an anti-inflammatory effect through suppression of the Th2 response and/or modulation of the Th1 response 19 …”
Section: Discussionmentioning
confidence: 99%